2019
DOI: 10.1016/j.advwatres.2019.103389
|View full text |Cite
|
Sign up to set email alerts
|

Dam break in rectangular channels with different upstream-downstream widths

Abstract: The classic Stoker dam-break problem [1] is revisited in cases of different channel widths upstream and downstream of the dam. The channel is supposed to have a rectangular cross section and a horizontal and frictionless bottom. The system of the shallow water equations is enriched, using the width as a space-dependent variable, together with the depth and the unit discharge, which conversely depend on both space and time. Such a formulation allows a quasi-analytical treatment of the system, whose solution is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The Authors found that the problem may exhibit multiple solutions if the flow impinging a rapid contraction is supercritical, and connected this finding with the hydraulic hysteresis phenomenon (Defina and Susin 2006). Valiani and Caleffi (2019) replicated the dam-break solution by Cozzolino et al (2018b), giving additional mathematical details that were implicit in Cozzolino et al (2018b). Finally, Goudiaby and Kreiss (2020) considered a class of Riemann problems at sudden expansions with Borda-Carnot losses and subcritical flow, demonstrating that there are initial conditions for which this problem has no solution.…”
Section: Introductionmentioning
confidence: 93%
“…The Authors found that the problem may exhibit multiple solutions if the flow impinging a rapid contraction is supercritical, and connected this finding with the hydraulic hysteresis phenomenon (Defina and Susin 2006). Valiani and Caleffi (2019) replicated the dam-break solution by Cozzolino et al (2018b), giving additional mathematical details that were implicit in Cozzolino et al (2018b). Finally, Goudiaby and Kreiss (2020) considered a class of Riemann problems at sudden expansions with Borda-Carnot losses and subcritical flow, demonstrating that there are initial conditions for which this problem has no solution.…”
Section: Introductionmentioning
confidence: 93%
“…This procedure provides an optimised approach, but it could requires a lot of mathematical effort to obtain the eigenstructure and can be used only with the specific set of PDEs. • Valiani and Caleffi [42] propose to use a path written in terms of the Riemann invariants. This choice could produce more complex and time-consuming integration since some models, such as the debris flow model, do not have an explicit version of the Riemann invariants.…”
Section: Possible Variantsmentioning
confidence: 99%
“…𝜕𝐔 𝜕𝑥 (42) where 𝜕𝐖∕𝜕𝐔 = 𝐁 −1 𝑊 is the inverse of matrix 𝐁 𝑊 . Therefore, we can define the new matrix for the non-conservative terms as: Ĥ𝑊 = 𝐇 𝑊 𝐁 −1 𝑊 (43) and we can obtain the following pseudo-Combined form:…”
mentioning
confidence: 99%
“…It can be seen that KV2 exhibits a relatively flat spectrum, with no noise components above 0.2 mm in amplitude, whereas KV1 exhibits noise up to almost 1 mm, particularly below 1 Hz. This can be important for studies of low-frequency phenomena or single events such as dam breaks [ 54 , 55 , 56 , 57 ] where the behaviour of interest is in the order of mm. In these cases, it would be an order of magnitude more reliable to use a KV2 sensor.…”
Section: Sensor Accuracy and Minimum Colourant Concentrationmentioning
confidence: 99%